Exercise stress test in apparently healthy individuals − where to place the finish line? The Ferrari corporate wellness programme experience. (29th August 2020) - Sirico, Felice; Fernando, Fredrick; Di Paolo, Fernando; Adami, Paolo Emilio; Signorello, Maria Grazia; Sannino, Giuseppe; Bianco, Antonio; Cerrone, Annunziata; Baioccato, Veronica; Filippi, Nicola; Ferrari, Umberto; Tuzi, Manuel; et al.
Abstract: Aims: The aim of our study was to assess the clinical significance of the exercise stress testing endpoints, namely 85% of maximal theoretical heart rate (MTHR), metabolic equivalent of task, and rating of perceived exertion (RPE), and their relation to electrocardiographic (ECG) changes in a healthy adult population. Methods: A cross-sectional study was conducted on 408 males and 52 females (mean age 39.4 ± 8.6 years) who performed the maximal cycle ergometer exercise stress test until volitional exhaustion, reporting the RPE score at 85% of MTHR and at peak exercise. Metabolic equivalents of task were indirectly calculated from the maximum workload and compared with the predicted values. Sitting torso-lead ECG and blood pressure were recorded at rest, during exercise and during recovery. Results: Of 460 participants, 73% exceeded 85% of MTHR. The RPE score represented the overall most significant endpoint of exercise stress testing, with the median value of 17 at peak exercise. ECG events were detected in 23/124 (18.5%) who reached ≤ 85% of MTHR and in 61/336 (18.2%) who achieved >85% of MTHR ( p = 0.92). In the latter group, 54% of ECG changes occurred at < 85% of MTHR and 46% at > 85% of MTHR ( p = 0.51). If the exercise stress testing had been interrupted at ≤ 85% of MTHR, almost half of the ECG events would have remained undetected and 35% of the cardiovascular abnormalities observed at the diagnostic follow-up would have remained undiagnosed. Conclusion: Terminating exercise stress testing before volitional exhaustion and an RPE score of 17 limits the test accuracy and reduces the possibility to detect cardiovascular abnormalities in apparently healthy adult populations.